EFEKTIVITAS LIDAH BUAYA SEBAGAI PEREKAT ALAMI PADA PESTISIDA NABATI DAUN SRIKAYA - Hamzah, Hamzah; Firmansyah, Amanda Patappari; Aisya, Nur; Angraini, Nur Afifah; Noerfitryani, Noerfitryani (Jurusan Budidaya Tanaman Perkebunan, Politeknik Pertanian Negeri Pangkajene Kepulauan, 2025)
The use of botanical pesticides is an environmentally friendly alternative to pest control. The weakness of botanical pesticides is their low adhesion to the leaf surface, thus reducing their effectiveness. This study aims to test the effectiveness of aloe vera gel as a natural adhesive in botanical pesticides made from soursop leaves. The study was conducted with a completely randomized design (CRD) using four doses of aloe vera gel (P0 = 0gr, P1 = 2gr, P2 = 4gr, P3 = 6gr) mixed with leaf extract. The mixture of extract and aloe vera was then sprayed on the feed. The parameters observed included the mortality of the test insects, the mortality rate and LC50. The results showed that treatment P3 (extract + 6gr aloe vera) caused the highest mortality of 2.4 individuals and was very significantly different compared to other treatments. The mortality rate 8-48 hours after observation showed that treatment P3 (extract + 6gr aloe vera) caused the highest and fastest mortality compared to other treatments. The treatment given to the test larvae showed body malformations such as stiffness and shortening of the body.